Sistem Kendali Pintu Air Otomatis Menggunakan Metode Fuzzy Mamdani - Gozali, Muhammad Syafei; Gautama, Aditya; Jefiza, Adlian; Diono, Diono; Rahmaini, Vika; Amri, Juhrial (Journal of Applied Electrical Engineering, 2024)
The research carried out developed a Fuzzy Mamdani-based irrigation sluice control system. The prototype built consists of an irrigation canal which is limited by a sluice gate. In the electronic circuit, ESP32 is used as a controller which is equipped with an ultrasonic sensor to detect the water level which is installed on the supply side and irrigation channel respectively. The sluice gate is moved using a DC motor. Fuzzy input consists of the height of the supply water level and irrigation channel water level as well as planting or harvest time, with a combination of 18 fuzzy rules. The results of level sensor testing carried out on four height targets with 80 trials, obtained an average percentage error for each sensor of 0.3% and 0.2% with an accuracy of 99.7% and 99.8%. The results of testing the sluice gate with a fuzzy system have 100% conformity with the condition of the water gate opening and closing with the level and time of planting and harvesting.